PENGARUH FAKTOR LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PNEUMONIA BALITA - Laliyanto Laliyanto; Nurjazuli Nurjazuli; Suhartono Suhartono (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
Pneumonia is a contagious infectious lung disease that is generally widespread and causes inflammation, reducing oxygenation, shortness of breath, and death. In Indonesia, pneumonia is still a health problem. The prevalence of pneumonia in Sleman Regency is 2.47%. The study aimed to determine the association and the amount of risk between physical environmental factors such as temperature and humidity in children under five rooms and the occurrence of pneumonia in five-year-old infants. The research method was an observational analytical with a Cross-Sectional survey approach. The sample in this study amounted to 100 children under five with an age range of 0-59 months. Samples were taken using the simple random sampling technique. The variables studied in this study were temperature and humidity variables associated with children under five with pneumonia. The study results were known to be associated with temperature variables with pneumonia in children under five p 0.04 and PR (95%CI) 3.00 (1.11 - 8.07). The measurement results on 100 respondents did not have a child under five room whose humidity qualified. The average yield of humidity is 76.02%Rh. A significant relationship exists between the temperature in the children under five room and the incidence of pneumonia under five. Humidity in all toddler rooms does not meet health requirements, with an average humidity of 76.02%Rh. Opening ventilation should be done periodically so that air circulation occurs so that the temperature and humidity in the children under five rooms can meet health requirements.